Platonism and the Bible(s) - Cook, Johann (HTS teologiese studies, 2022)
A relatively recent development in Septuagint studies is a focus on the alleged influence of Platonism on the Bible(s) (Hebrew Bible/Old Testament and the Septuagint). This article argues that Hellenism did in fact have an impact on Judaism. There are basically two groups of views on this issue. The first is that of the so-called minimalists, who make practically no allowance for freedom by the translators, and the second is that of the so-called maximalists, who believe that translators are relatively independent authors and interpreters. As far as the relationship between Judaism and Platonism is concerned, some scholars think Greek thought, specifically in the form of Platonism, had a determinative influence on Judaism, but others are not convinced. This article opts for a middle of the road point of view. It accepts that Hellenism had a definite impact on Judaism but it was not as extensive as stated by some.Contribution: This research fits into the scope of HTS Teologiese Studies/Theological Studies because it has made a study of the alleged impact of Platonism on Judaism. It finds that this impact is based on speculation, especially, by two authors: Evangelia Dafni and Russell Gmirkin.